Winning Modern Wars : Iraq, Terrorism, and the American Empire - Clark, General Wesley K. (New York PublicAffairs, 2003)
In Winning Modern Wars, he writes about how the issues and principles discussed in his earlier book were evident in Afghanistan and Iraq, and will apply wherever the war on terrorism may take us next, providing a frank and revealing analysis of the gains, risks, and shortfalls of America's current approach and offering informed alternatives. What Clark, an admired military analyst on CNN and one of the most decorated and influential officers of his generation, has to say on our national plans and tactics$1 (Band the lessons of empire$1 (Bis invaluable, reminding us that as we celebrate our successes, we must also tend to their consequences.s
Include Index,Appendix and Notes.
Discusses America's involvement in Iraq, including the risks, triumphs, and repercussions, and offers alternatives to future dealings with Iraq and the War on Terrorism.
Keywords: War on Terrorism (2001-2009) -- Iraq War (2003-2011) -- United States -- Foreign Relations